COMPUTER DYNAMICS MODELING OF TRANSPORT FACILITIES WITH ANTI-LOCKING AND ANTI-SLIPPAGE SYSTEMS - N. N. Hurski; Y. I. Slabko; R. I. Fourounjiev; A. L. Homich (Наука и техника)
The paper considers a methodology for testing anti-locking system (ALS) of new generation. Results of computer  dynamics  modeling of automobile motion at braking with ALS and without ALS are given in the paper. The paper also contains an analysis of  basic characteristics: a braking distance, a value of longitudinal delay, an influence of modulator speed on the efficiency of a braking